Certain finite expansions associated with a basic analogue of the G-function - Saxena, R.; Kumar, R. (Revista Técnica da Faculdade de Engenharia da de Zulia)
In this paper the authors derive certain finite expansion formulae associated with a basic analogue of MeijerÂ´s G-function. The results proved in this paper are the extensions of the results given earlier by R. P. Agarwal [1] and N. Agarwal [2].